Determinants of Purchase Decisions toward Influencer-Promoted Organic Creams among Students on Social Media - Emmanuel Olukunle Olumuji; Adebola Solate Olanrewaju; Kamoru Aremu Salaudeen (LSPR Institute of Communication & Business, 2026)
This study examines the determinants of purchase decisions toward influencer-promoted organic creams among female university students on social media in Abeokuta, Ogun State, Nigeria. Specifically, the study examines the social media platforms through which students most frequently encounter influencer-endorsed organic cream advertisements and factors shaping purchase decisions, and the challenges associated with influencer marketing within Nigeria’s beauty industry. A mixed-methods research design was employed, combining a descriptive survey and in-depth interviews. Quantitative data were obtained from 380 female students drawn from Chrisland University and the Federal University of Agriculture, Abeokuta (FUNAAB), using a structured questionnaire administered via Google Forms. Qualitative data were generated through in-depth interviews with five organic skincare industry experts and analysed thematically. The findings indicate that TikTok and Instagram are the most prominent platforms for influencer-endorsed organic cream advertising, with their visually rich and interactive features significantly enhancing audience engagement. Purchase decisions were largely influenced by perceived product effectiveness, peer endorsement, and ease of access to purchase links embedded in influencer content. The study concludes that social media influencers play a significant role in shaping organic cream purchase behaviour among female university students; however, their influence is largely dependent on perceived authenticity, transparency, and relevance to consumer needs. The study recommends that marketers prioritise TikTok and Instagram for influencer campaigns, emphasise authentic product testimonials, and promote ethical advertising practices to strengthen consumer trust and improve marketing outcomes in Nigeria’s beauty industry.